2013
DOI: 10.1093/cvr/cvt006
|View full text |Cite
|
Sign up to set email alerts
|

The new antiarrhythmic drug vernakalant: ex vivo study of human atrial tissue from sinus rhythm and chronic atrial fibrillation

Abstract: Rate-dependent block of Na(+) channels represents the main antiarrhythmic mechanism of vernakalant in the fibrillating atrium. Open channel block of early transient outward currents and IK,ACh could also contribute.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
87
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 98 publications
(101 citation statements)
references
References 38 publications
(50 reference statements)
9
87
0
2
Order By: Relevance
“…10 Accordingly, the data from the present study indicate that both drugs slow conduction in all layers in the LV wall to a similar extent. This implicates that Vernakalant also has a potent effect on sodium currents, which is in line with a recent study by Wettwer et al 17 that strongly suggests that the main mode of action of Vernakalant is through the blockage of sodium channels instead of the assumed more potent and atrial selective blockage of I Kur .…”
Section: Electrophysiological Effectssupporting
confidence: 89%
“…10 Accordingly, the data from the present study indicate that both drugs slow conduction in all layers in the LV wall to a similar extent. This implicates that Vernakalant also has a potent effect on sodium currents, which is in line with a recent study by Wettwer et al 17 that strongly suggests that the main mode of action of Vernakalant is through the blockage of sodium channels instead of the assumed more potent and atrial selective blockage of I Kur .…”
Section: Electrophysiological Effectssupporting
confidence: 89%
“…158,159 However, recent studies reported reduced peak I Na in patients with AF that could contribute to re-entry-promoting conduction slowing. 160,161 In addition, persistent/late I Na is increased in some studies. 160 Although the exact functional consequences are presently unknown, patients with early-onset lone AF also exhibit a high prevalence of Na + channel mutations that increase persistent/late I Na .…”
Section: Conduction Abnormalities and Structural Remodelingmentioning
confidence: 98%
“…Only small, about 10 to 20% changes in I Na density in atrial myocytes of patients with chronic AF have been detected [151][152]. In atrial tachycardia induced AF animal models, however, a marked decrease in I Na was observed [153].…”
Section: +mentioning
confidence: 99%